Reconstruction of the road bridge in Żórawina as the example of ecological, aesthetic and economic values of soil-steel structures - Antoniszyn, Grzegorz (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
The article presents issues related to the reconstruction of the road bridge in the village Żórawina. An existing bridge was replaced by a new soil-steel structure. The adopted solutions, which fulfill the guidelines of conservator’s protection, allowed making aesthetic and simultaneously economically efficient bridge structure. The time needed to carry out the investment was also a very important factor in determining the final design solutions.